ANALISIS PENGARUH PROFITABILITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PADA TAHUN 2011-2014 - Abdullah Rakhman; elisabeth vita mutiarawati; david tanujaya (Jurnal Ekonomi Perusahaan, 2016)
The aim of this study is to determine the relationship between profitability ratios, which are Return on Asset, Net Profit Margin, Return on Equity, and capital structure toward the company values. This research using non-probability sampling method with purposive sampling method. This research using SPSS 20 to processing the data and result of this research showed that profitability ratio has a significant influence and positive impact toward the company values, while the capital structure has a significant influence and a negative impact toward the company values.